Analysis of Incidence and Risk Factors of Complicated Acute Appendicitis in Children: Evidence From a Tertiary Pediatric Center - Sina Azadnajafabad; Faraha Zahra Awan; Bahar Ashjaei; Hosein Alimadadi; Mahsa Soti Khiabani (International Journal of Pediatrics)
Conclusions: Laboratory parameters, specifically WBC count, neutrophil count, and CRP levels, are significant independent predictors of complicated AA in pediatric patients. These findings could assist in the timely diagnosis and management of children suspected of having AA in clinical practice.